Green chemistry and engineering : a path to sustainability - Marteel-Parrish, Anne.; Abraham, Martin A., 1961- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
'Although many were skeptical of the green chemistry movement at first, it has become a multimillion-dollar business. In preventing the creation of hazardous wastes, laboratories and corporations can save millions in clean up efforts and related health costs. This book supplies students with concepts commonly taught in undergraduate general chemistry and general engineering courses, but with a green perspective. It is unique in presenting an integrated discussion of green chemistry and engineering from first principles - not as an afterthought. Real-world examples show creative problem solving based on the latest issues'--
'This book presents the same concepts commonly taught in undergraduate general chemistry and general engineering courses (organic, inorganic, analytical, and biochemistry, with applications to environmental and materials science) but with a green perspective'--
Includes bibliographical references and index.
Keywords: Green chemistry